Can Highlanders FC break the jinx? Contesting press discourses on Highlanders FC's nine-year failure in the 'battle of Zimbabwe'. Issue 4 (2nd October 2017) - Ncube, Lyton; Moyo, Ronald
Abstract: This study shows contesting media discourses in the coverage of Zimbabwe's most enduring football rivalry. Like other countries across the globe, Zimbabwe has unique football rivalries and derbies from the local level to the national stage. Popularly known as the 'battle of Zimbabwe', the Dynamos FC and Highlanders FC rivalry is complex and far-reaching in impact as it is encoded with the discourse of the everyday. However, studies analysing this rivalry from media studies lens are few and far between. This article analyses the coverage of the 'battle of Zimbabwe' in two national daily newspapers – The Herald and Chronicle . Both newspapers are published by the Zimbabwe Newspapers (Zimpapers) group and are state controlled. The study focuses on the framing of selected matches involving the two teams played between 2007 and 2015, when Highlanders FC failed to beat Dynamos FC in all their Premier Soccer League matches. The study shows competing ideologies and contesting discourses in the two newspapers' framing of Dynamos FC's perennial dominance and Highlanders FC's failure in the 'battle of Zimbabwe'. The contestation between the two newspapers show the manifestation of the Dynamos FC and Highlanders FC rivalry in newsrooms, reflecting sports journalists' attitudes of attachment and bonds of loyalty.